Correction to: Evaluation of the tolerance and biotransformation of ferulic acid by Klebsiella pneumoniae TD 4.7 (Brazilian Journal of Microbiology, (2021), 10.1007/s42770-021-00462-x) - dos Santos, Maitê Bernardo Correia [UNESP]; Scarpassa, Josiane Aniele [UNESP]; Monteiro, Diego Alves [UNESP]; Ladino-Orjuela, Guillermo [UNESP]; Da Silva, Roberto [UNESP]; Boscolo, Mauricio [UNESP]; Gomes, Eleni [UNESP] (Springer Nature, 2021)
In the original publication of the article, the following sentences as the last part of the “Determination of ferulic acid decarboxylase activity” were missing. The enzymatic activity assays were measured in a reaction mixture composed of 0.05 mL of the extracts (10% v v-1) and 0.45 mL of a solution composed of 0.5 g L-1 of ferulic acid. The reaction mixture was incubated at 30 °C for 15 min. The activity of the ferulic acid decarboxylase enzyme was measured by the reduction of ferulic acid and the formation of 4-vinylguaiacol (µmol). One unit of activity was defined as the production of 1 µmol of 4-vinylguaiacol per min. For the determination of specific activity, the total enzyme unit (U) and the biomass weight (g) were considered as a reference for the total cell used in the reaction. Additionally, the total protein was quantified according to the Bradford method, using bovine serum albumin as the standard [26].